Exploring households’ access and utilization of antibiotics for their livestock: a cross-sectional study in Ghana and Burkina Faso - Cama i Gibernau, Elisenda; Krumkamp, Ralf; Aglanu, Leslie Mawuli; Zakane, Alphonse; Jahn, Albrecht; Sié, Ali; Amuasi, John Humphrey; Souares-Coutant, Aurélia (Journal of global antimicrobial resistance, 2025)
Objectives - The irrational use of antibiotics in animals contributes to antimicrobial resistance. This study examines factors influencing access to veterinary services and antibiotic use among livestock-owning households in the Asante Akim North District, Ghana, and the Nouna District, Burkina Faso. - Methods - In Burkina Faso, a simple randomization was carried out, whereas in Ghana, double-stage cluster sampling was applied. A cross-sectional survey collected sociodemographic and economic data, along with information on veterinary access and antibiotic use. The data collection was conducted between February and March 2023 in Ghana, and from July to November 2023 in Burkina Faso. Data analysis used descriptive statistics and logistic regressions. - Results - Among the sampled households, 415 (37.3%) in Ghana and 521 (51.5%) in Burkina Faso owned livestock. Antibiotics were administered to both sick and healthy animals, mainly amoxicillin (22%) in Ghana and tetracycline (7.25%) in Burkina Faso. In Ghana, individuals with no religious affiliation (adjusted odds ratio [aOR] = 0.06, 95% confidence interval [CI] = 0.01-0.48, P = 0.008), and semi-urban residents (aOR = 0.34, 95% CI = 0.21-0.54, P = > 0.001) had lower access to veterinary services, whereas those in the highest socioeconomic quartile had greater access (aOR = 3.38, 95% CI = 1.82-6.27, P = > 0.001). In Burkina Faso, socioeconomic status (SES) and residence are confounding factors. Stratified analysis showed semi-urban residents and wealthier groups had better veterinary access, unlike rural populations. - Conclusions - There is a need to address antibiotic use through stronger regulations, improved access to veterinary services, and targeted education programs to prevent antimicrobial resistance (AMR) among populations in West Africa.